The Effectiveness of Restorative Justice in Overcoming Overcrowding in Correctional Institutions According to Law Number 22 of 2022 Concerning Corrections - Anwar, Rosyian; Arpangi, Arpangi (UNISSULA Semarang, 2025)
Abstract. This study aims to determine and analyze the situation, causes and impacts of overcrowding that occurs in prisons/detention centers in Indonesia, to determine and analyze the effectiveness of the implementation of restorative justice in overcoming overcrowding in prisons/detention centers in Indonesia according to Law Number 22 of 2022 concerning Corrections. To determine and analyze alternative solutions and strategies for implementing restorative justice in overcoming overcrowding in prisons/detention centers in Indonesia in the future. The resolution of violations of the law through the criminal justice system tends to be very prison-oriented. Every criminal violation always ends in imprisonment. The concept of prison as ultimum remedium (last resort) shifts to premium remedium (main resort) and of course the final result is that prisons face a latent problem called overcrowded or overcapacity. The specifications of this study are included in the analytical descriptive research environment, with a normative approach method, with the type and source of primary data from interviews with informants and secondary data covering various kinds of literature and laws and regulations in Indonesia. The results of the study show that the overcrowded situation has placed Indonesia at an extreme point with an excess of 188%. The overcrowded situation has an impact on the emergence of human rights, security and health problems for its residents. In addition, the overcrowded situation also has an impact on the families of suspects/convicts, society and the State. The effectiveness of the implementation of restorative justice in overcoming overcrowding in prisons/prisons in Indonesia according to Law Number 22 of 2022 concerning Corrections has not shown a significant impact. alternative solutions and future strategies, namely reorientation of criminal punishment, making non-prison criminal policies more effective, revising regulations that hinder outflows.